2022
DOI: 10.1039/d2tc00326k
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the circularly polarized luminescence of polymer-stabilized cholesteric liquid crystal films using chiral dopants

Abstract: In this work, a tetraphenylethene and imidazo[1,2-a]pyridine-attached difluoroboron β-diketonate triad TPE-BF2acac-MeIP has been synthesized. The highly emissive compound TPE-BF2acac-MeIP exhibits significant aggregation-induced emission (AIE) and mechanofluochromism (MFC) properties and can...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…15 We have prepared a series of PSCLC films by adding tetraphenylethylene (TPE)-based fluorescent molecules into CLCs, and in situ photopolymerisation subsequently. 16 High g lum values (| g lum | of up to 0.61) of the CPL-active materials were induced by the long-range ordered supramolecular helical structures of PSCLCs. Moreover, the CPL-active organic–inorganic hybrid silica films embedded with a TPE derivative were prepared.…”
Section: Introductionmentioning
confidence: 99%
“…15 We have prepared a series of PSCLC films by adding tetraphenylethylene (TPE)-based fluorescent molecules into CLCs, and in situ photopolymerisation subsequently. 16 High g lum values (| g lum | of up to 0.61) of the CPL-active materials were induced by the long-range ordered supramolecular helical structures of PSCLCs. Moreover, the CPL-active organic–inorganic hybrid silica films embedded with a TPE derivative were prepared.…”
Section: Introductionmentioning
confidence: 99%
“…Since the reflectance of these films was low in the range of the emission band, the emitted CPL could be attributed to the contribution of the chiral induction of CLCN structures. 50,51 When the concentration of R5011 was 1.8 wt %, the emission band partially overlapped with the reflection band, and a g lum value of −0.60 was achieved (Figure 3c). As the reflection band shifted far away from the main emission band, small |g lum | values were obtained.…”
Section: Free-standing Clcn Filmsmentioning
confidence: 99%
“…We previously successfully synthesized several fluorescent dyes and embedded them into CLC mixtures. After polymerization, emissive CLC polymer networks (CLCNs) with vivid structural colors were obtained. Very recently, composite films were built by stacking a fluorescent layer and a CLCN layer. , It was demonstrated that CLCN films with high reflectance could serve as chiral optical filters, and the composite film emitted CPL with a large | g lum | value up to 1.63 .…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Lu et al prepared a kind of AIE and mechanofluochromism-active triad dye, which was applied for latent fingerprint visualization. [219] The polymer-stabilized cholesteric liquid crystals films were obtained by adding the dyes to cholesteric liquid crystal matrix for photopolymerization. The resulting films exhibited tunable CPL with g lum values of up to 0.61.…”
Section: Chiral Component and Luminescent Component: Non-covalent Int...mentioning
confidence: 99%